Check the effects: systematic assessment of antipsychotic side-effects in an inpatient cohort - Caroline Hynes; Stephen McWilliams; Mark Clarke; Ita Fitzgerald; Larkin Feeney; Mark Taylor; Fiona Boland; Dolores Keating (SAGE Publishing, 2020)
Background: Antipsychotics are associated with a range of side-effects that can influence patients' subjective well-being negatively resulting in poor adherence. In order to limit the negative consequences of side-effects, they should be regularly systematically assessed. The aim of this study was to systematically assess antipsychotic side-effects in an inpatient cohort using validated rating scales. Methods: Eligible individuals prescribed an antipsychotic for at least 2 weeks were invited to have their side-effects assessed systematically. Results: A total of 208 individuals were assessed systematically for antipsychotic side-effects; 71.5% ( n  = 138) stated that they had not reported side-effects to their clinician prior to the assessment. The most commonly reported side-effects were daytime drowsiness (75%), dry mouth (58.2%) and weight gain (50.0%), while the most distressing side-effects reported were erectile dysfunction (35.0%), sexual dysfunction (26.3%) and amenorrhoea (26.3%). There was no evidence of an association between side-effect severity/number of side-effects reported/distress caused by those taking high dose/combination antipsychotics versus standard dose monotherapy. Conclusion: Side-effects must be regularly and systematically assessed using a validated rating scale. As distress caused by side-effects plays a major role in non-adherence, assessment should examine distress and data on distressing side-effects should be available to those choosing an antipsychotic. Given the lack of correlation between high dose/combination antipsychotics and side-effects, treatment should be tailored to the individual based on response/tolerance and dose reduction/avoidance of polypharmacy should not be recommended to minimise side-effects.